2014
DOI: 10.1111/mice.12073
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Construction Scheduling Simulation Algorithm

Abstract: A scheduler can accelerate a construction project by setting up overlapping activities. Activities are said to be overlapping if two activities that are normally executed in sequence are performed in parallel, the successor starting before the end of the predecessor. This article presents a novel method that identifies an optimal overlap rate between critical activities to provide a time‐cost trade‐off analysis, hence reducing completion time and cost without allocating additional resources. This method is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…Similarly, Lim et al. () take the concurrent feature of a scheduling plan to accelerate a construction project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Lim et al. () take the concurrent feature of a scheduling plan to accelerate a construction project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other models have, for simplicity, assumed the probabilities can be added [39,49], or have used the longest average rework duration instead [50], but those simplifications are not correct.…”
Section: The Multi-predecessor Case and Cascade Of Overlapsmentioning
confidence: 99%
“…Throughout the analyzed literature, researchers have shown that the GPRs are needed to formulate “ real‐life constraints ” (Schwindt, ), and that fragmentation and overlapping of processes and activities is very effective in improving the estimation of the project makespan for the Unconstrained Project Scheduling Problem (PSP) (Valls et al., ; Ponz‐Tienda et al., ) and Constrained PSP (Quintanilla et al., ), as well as for fast‐tracking complex construction projects (Srour et al., ) by setting up overlapping activities (Lim et al., ). Preemption as a solution for the fragmentation has been widely studied in manufacturing and services environments.…”
Section: Literature Reviewmentioning
confidence: 99%